IMPLEMENTING CONTEXTUAL TEACHING AND LEARNING APPROACH TO IMPROVE STUDENTS’ CONCEPTUAL UNDERSTANDING ON MATHEMATICS - Kasmiati Kasmiati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the students' low understanding on the concepts and the students’ difficulty in linking the knowledge to their daily life. Implementing contextual teaching and learning approach was expected to improve students' conceptual understanding. This research was a classroom action research conducted to third grade students at SDN Negeri 002 Sungai Salak, Kecamatan Tempuling. The research was conducted in the even semester of the academic year 2018-2019. The instrument was a concept understanding test. The results showed that the average score of students' conceptual understanding in cycle I was 68.43 with sufficient category. Then, the classical completeness was 56.25%. In cycle II, the average score of the students' conceptual understanding was 72.81 with classical completeness reaching 93.75%. Based on the research results, it was concluded that contextual teaching and learning approach improved the students’ conceptual understanding at grade III SD Negeri 002 Sungai Salak, Kecamatan Tempuling.